The mediating role of job satisfaction in the relationship between ethical leadership and person-job fit on teacher performance at SMK Taruna Abdi Bangsa Winong - Fardani, Irvan; Riptiono, Sulis (Trigin Publisher, 2025)
This study examines the effects of person-job fit and ethical leadership on teacher performance using job satisfaction as a mediating variable. This study is motivated by the phenomenon of suboptimal teacher performance in vocational high schools, which is thought to be influenced by the principal's leadership style and the suitability of the teacher's role to his job. The purpose of this study is to determine the direct and indirect effects of ethical leadership and person-job fit on teacher performance, with job satisfaction as a mediator. SEM-PLS is used to analyze the quantitative approach and questionnaire used in the study, which was conducted at SMK Taruna Abdi Bangsa. The sample in this study amounted to 31 teachers selected through a total sampling technique. The research findings indicate that ethical leadership and person-job fit have a significant influence on teacher performance and job satisfaction. However, work happiness does not operate as a mediator in the relationship between ethical leadership or person-job fit and teacher performance, and it has no appreciable effect on teacher performance. The study emphasizes the significance of leadership and job alignment in improving teacher performance, even though job satisfaction is not a useful mediator in this situation. The implications of this research are expected to be a reference for school management in developing strategies to improve teacher performance through ethical leadership and teacher placement according to their expertise.